Proteomic profiling of plasma-derived small extracellular vesicles: a novel tool for understanding the systemic effects of tick burden in cattle. (19th January 2022) - Turner, Natalie; Abeysinghe, Pevindu; Peiris, Hassendrini; Vaswani, Kanchan; Sadowski, Pawel; Cameron, Nick; McGhee, Nathanael; Logan, Jayden; Mitchell, Murray D
Abstract: Cattle ticks pose a significant threat to the health and profitability of cattle herds globally. The investigation of factors leading to natural tick resistance in cattle is directed toward targeted breeding strategies that may combat cattle tick infestation on the genetic level. Exosomes (EX s), small extracellular vesicles (EV s) of 50 to 150 nm diameter, are released from all cell types into biofluids such as blood plasma and milk, have been successfully used in diagnostic and prognostic studies in humans, and can provide essential information regarding the overall health state of animals. Mass spectrometry (MS ) is a highly sensitive proteomics application that can be used to identify proteins in a complex mixture and is particularly useful for biomarker development. In this proof of principle study, EXs were isolated from the blood plasma of cattle ( Bos taurus ) with high (HTR ) and low tick resistance (LTR ) ( n = 3/group). Cattle were classified as HTR or LTR using a tick scoring system, and EXs isolated from the cattle blood plasma using an established protocol. EXs were subjected to MS analysis in data-dependent acquisition mode and protein search performed using Protein Pilot against the B. taurus proteome. A total of 490 unique proteins were identified across all samples. Of these, proteins present in all replicates from each group were selected for further analysis (HTR = 121; LTR = 130). Gene ontology analysis was performed using PANTHER GO online software tool. Proteins unique to HTR and LTR cattle were divided by protein class, of which 50% were associated with immunity/defense in the HTR group, whereas this protein class was not detected in EXs from LTR cattle. Similarly, unique proteins in HTR cattle were associated with B-cell activation, immunoglobins, immune response, and cellular iron ion homeostasis. In LTR cattle, unique exosomal proteins were associated with actin filament binding, purine nucleotide binding, plasma membrane protein complex, and carbohydrate derivative binding. This is the first study to demonstrate that MS analysis of EXs derived from the blood plasma of HTR and LTR cattle can be successfully applied to profile the systemic effects of tick burden. Lay Summary: Cattle ticks are a significant burden to cattle industries globally. Current methods to treat cattle ticks are costly and inefficient in the long term. It has been noted that while some cattle may exhibit a natural resistance to ticks, others carry a heavy tick burden. The study of small extracellular vesicles, or exosomes (EXs), isolated from cattle blood plasma provides a noninvasive way of analyzing changes at the cellular level and may be of use in understanding the systemic effects of tick burden or factors leading to natural resistance. The aim of this study was to assess high (HTR) and low tick resistance (LTR) cattle identified using a tick burden scoring system by analyzing the protein content of circulating EXs via qualitative proteomics analysis. We found that a class of proteins related to defense/immunity comprised 50% of proteins unique to HTR cattle, while this protein class was not detected in proteins unique to LTR cattle. Additionally, epidermal growth factor–calcium-binding protein domains were 2-fold increased in LTR cattle compared with HTR cattle, indicating a possible mechanism for widespread metabolic change. This is the first study to employ proteomic analysis of exosomal cargo as an approach to understanding the systemic effects of tick burden in cattle. Abstract : Small extracellular vesicles (EVs) of size ~50 to 150 nm have been isolated and enriched from the blood plasma of cattle exhibiting high and low natural resistance to tick infestation. Proteomic analysis of these small EVs by mass spectrometry has provided valuable information regarding the systemic effects, and particularly the immune challenges, of tick burden on animals exhibiting low tick resistance.